Pengangguran orang kurang upaya dan pelaksanaan Program Perkhidmatan Job Coach di Kedah - Noor Fatihah, Mat Radzi (2025)
The issue of unemployment among persons with disabilities persists, even though they should not face discrimination in employment. The key questions that arise concern the challenges faced by persons with disabilities in securing employment in the open employment market and the difficulties in accessing job support through the Program Perkhidmatan Job Coach (PPJC) implemented by the Malaysian government. Therefore, this study examines the issue of unemployment among persons with disabilities and the implementation of employment support, focusing on the services provided by PPJC in the state of Kedah, Malaysia. Specifically, the study sets out four main objectives: (1) To examine the challenges faced by persons with disabilities in their efforts to secure employment; (2) To investigate the factors contributing to employers' reluctance to hire persons with disabilities in their organizations; (3) To analyze the role of the PPJC in enhancing job satisfaction among persons with disabilities; and (4) To assess stakeholders' perspectives on the effectiveness of the PPJC in helping persons with disabilities obtain employment that aligns with their abilities and needs. In line with the study’s aims and objectives, data collection is conducted qualitatively through interviews, document analysis, and indirect observation. The study sample consists of 14 respondents, including policymakers and implementing officers from PPJC, employers who hire persons with disabilities, and persons with disabilities who have secured employment with the program's assistance. The findings of this study indicate that government policies and support, education, employer attitudes, self-confidence, as well as assistance and services are identified as challenges faced by persons with disabilities in employment. This study also shows that job satisfaction among persons with disabilities is positively influenced by the PPJC. The achievement of all four objectives can serve as a guideline for all parties, including government agencies and employers seeking to hire persons with disabilities. Additionally, it also serves as a key element in improving the future implementation of employment support through PPJC.